The Philippine urban poor - Doherty, John F. (Philippine studies occasional paper, 1985)
"This occasional paper aims to provide an outlet for scholarly work on Philippine-related topics. The series is broadly interdisciplinary but manuscripts touching on specialized subjects on the humanities, social sciences, and other aspects of Philippine life and culture will also be considered."--Foreword